2020
DOI: 10.1021/acs.inorgchem.0c00136
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Electrochemical Trends in Divalent Lanthanides through Modulation of Coordination Environment

Abstract: Due to the importance of both visible-light luminescence and lanthanides in modern society, the influence of the ligand environment on complexes of YbII were studied and compared with analogous complexes of EuII. Four ligands with systematically varied electronic and steric characteristics were used to probe the coordination environment and electronic and redox properties of the corresponding YbII-containing complexes. Strong-field nitrogenous donors gave rise to bathochromic shifts, leading to visible-light a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 70 publications
5
65
1
Order By: Relevance
“…Cryptand complexes of the traditional divalent lanthanoids were some of the first to be investigated, with the benefit of encapsulation aiding in the stabilization of Ln II state and facilitating studies of luminescent properties through prevention of quenching by deterring inner sphere solvent coordination [58] . A recent spectroscopic and electrochemical investigation of Eu II and Yb II complexes ([Yb(N 8 L crypt )] ( 8 ), [Yb(Me 6 N 8 L crypt )] ( 9 ), [Yb(O 4 N 2 L crypt )] ( 10 ), and [Yb(PhO 4 N 2 L crypt )] ( 11 ); Scheme 1) probed the impact on the redox properties of systematic variation of the electronic and steric properties of cryptand ligands [49] . Although the Eu II analogues were previously reported, [58b,c, 59] these had not yet been investigated for Yb.…”
Section: Lanthanoid Complexes With Unusual Lanthanoid Oxidation Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptand complexes of the traditional divalent lanthanoids were some of the first to be investigated, with the benefit of encapsulation aiding in the stabilization of Ln II state and facilitating studies of luminescent properties through prevention of quenching by deterring inner sphere solvent coordination [58] . A recent spectroscopic and electrochemical investigation of Eu II and Yb II complexes ([Yb(N 8 L crypt )] ( 8 ), [Yb(Me 6 N 8 L crypt )] ( 9 ), [Yb(O 4 N 2 L crypt )] ( 10 ), and [Yb(PhO 4 N 2 L crypt )] ( 11 ); Scheme 1) probed the impact on the redox properties of systematic variation of the electronic and steric properties of cryptand ligands [49] . Although the Eu II analogues were previously reported, [58b,c, 59] these had not yet been investigated for Yb.…”
Section: Lanthanoid Complexes With Unusual Lanthanoid Oxidation Statesmentioning
confidence: 99%
“…Overall, similar trends in the order of redox potentials for the Yb series and the Eu series were observed, with the processes for the Yb II complexes exhibiting more negative potentials than the Eu II . The study revealed that nitrogenous donors gave rise to bathochromic shifts resulting in visible light absorption [49] …”
Section: Lanthanoid Complexes With Unusual Lanthanoid Oxidation Statesmentioning
confidence: 99%
“…Evidence that the ligand environment alters the Ln­(III)/Ln­(II) redox potential is abundant. Cryptands with soft donor atoms can stabilize Eu­(II) and Yb­(II) . Eu­(III) centers in different ligand environments may differ in their redox potentials by as much as 1.4 V .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of such metal complexes have been crystallographically-characterized involving both divalent and trivalent ions usually with one or two additional coordinated ligands that could be anions or neutral species. Examples include [Ln II (crypt)(THF) x ][Cp′ 3 Ln] (x = 1, Ln = Sm, Eu; x = 0, Ln = Yb), 30 [Sm II (crypt) (DippForm)][DippForm] (DippForm = N,N′-bis(2,6-diisopropylphenyl)-formamidinate), 31 [Sm II (crypt)(PCO) 2 ], 31 [Eu II (crypt) Cl][Cl], 32 [Yb II (crypt)I][I], 33 [Ln III (crypt)(THF)][BPh 4 ] 2 (Ln = Sm, Eu), 34 [La III (crypt)Cl 2 ][Cl], 35 [Ln II (crypt)(DMF) x ][X] 2 (x = 2, Ln = Sm, Eu; x = 1, Ln = Yb; X = I, BPh 4 ), 36 [Ln III (crypt)(OTf) 2 ][OTf] and [Ln II (crypt)(OTf) 2 ] (Ln = Nd, Sm) 37 among others. [38][39][40][41][42] We report here a new coordination mode for crypt with rareearth metal ions that is intermediate between the two modes described above, i.e.…”
Section: Introductionmentioning
confidence: 99%